Kesiapan Masuk Sekolah Dasar dan Motivasi Berprestasi Siswa SD Negeri di Desa Trompoasri Sidoarjo - Isnaini, Nurul; Mariyati, Lely Ika (Web of Scientist International Scientific Research Journal, 2023)
The research was conducted because of the phenomenon of the readiness of school children to enter elementary school which was carried out by grade 1 children of public elementary schools in Trompoasri village. The purpose of this study was to determine the relationship between elementary school readiness and achievement motivation of public elementary school students in Trompoasri village, Sidoarjo. The hypothesis put forward is that there is a positive relationship between children's readiness to enter elementary school and achievement motivation in grade 1 elementary school students. The sample in this study amounted to 49 students. Sampling was carried out using accidental sampling technique. Data analysis used the product moment correlation technique from Pearson with the hellp of the SPSS 26.0 program. The results of the analysis of this study show a correlation coefficients of rxy = 0.334 (significance 0.019 <0.05), which means that the research hypothesis is accepted, namely that there is a positive relationship between children's readiness to enter primary school and achievement motivation in grade 1 students at SDN Trompoasri Village. This means that the higher the child's readiness to enter elementary school, the higher the achievement motivation, and vice versa, the lower the child's readiness to enter elementary school, the lower the achievement motivation.